2014
DOI: 10.2478/bvip-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

Pathomorphological changes in the alimentary system of Japanese quails naturally infected with Eimeria tsunodai

Abstract: The aim of this study was to investigate pathomorphological changes in the duodenum, jejunum, ileum, and caecum of Japanese quails naturally infected with Eimeria tsunodai. Samples of the intestines were collected from 6-week-old cockerels and hens before laying and from laying quails aged 12, 24, and 48 weeks. The tissue sections were stained with haematoxylin and eosin, PAS method according to McManus, and Ziehl-Neelsen method. Morphometric and morphological analyses of coccidia revealed that Eimeria tsunoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
1
3
0
2
Order By: Relevance
“…Atinge o epitélio intestinal dos vários grupos de aves, representado por lesões deixadas na área de fixação do parasita (Soave, 2011;Vita et al 2019). Há quatro espécies de Eimeria que podem ser identificadas em codornas (Teixeira et al, 2004;Mohammad, 2012), baseadas na especificidade do local de desenvolvimento, entre elas: E. tsunodai, com desenvolvimento quase exclusivo no ceco (Tsutsumi, 1972), E. uzura (Tsunoda & Muraki, 1971) e E. bateri (Bhatia, Pandey & Pande, 1965) que habitam preferencialmente o duodeno e jejuno, respectivamente (Teixeira et al 2004, Gesek et al 2014. A presença de oocistos do gênero Eimeria foi visualizada, como no estudo relatado, em C. japonica em Manaus, Brasil (Monte et al 2018).…”
Section: Resultsunclassified
“…Atinge o epitélio intestinal dos vários grupos de aves, representado por lesões deixadas na área de fixação do parasita (Soave, 2011;Vita et al 2019). Há quatro espécies de Eimeria que podem ser identificadas em codornas (Teixeira et al, 2004;Mohammad, 2012), baseadas na especificidade do local de desenvolvimento, entre elas: E. tsunodai, com desenvolvimento quase exclusivo no ceco (Tsutsumi, 1972), E. uzura (Tsunoda & Muraki, 1971) e E. bateri (Bhatia, Pandey & Pande, 1965) que habitam preferencialmente o duodeno e jejuno, respectivamente (Teixeira et al 2004, Gesek et al 2014. A presença de oocistos do gênero Eimeria foi visualizada, como no estudo relatado, em C. japonica em Manaus, Brasil (Monte et al 2018).…”
Section: Resultsunclassified
“…According to Teixeira et al (2004) and Mohammad (2012), four species of Eimeria can be found in quails; E. tsunodai Tsutsumi, 1972, E. uzura Tsunoda et Muraki, 1971, E. bateri Bhatia, Pandey et Pande, 1965and E. fluminensis Teixeira et Lopes, 2002. Based on the specificity of the development site of Eimeria in quails, cecal infection can be associated with E. tsunodai, since, according to Tsutsumi (1972), Gesek et al (2014) this species has almost exclusive development in the cecum, whereas E. bateri, and E. uzura preferably inhabit portions of the duodenum and jejunum respectively (Teixeira et al 2004, Gesek et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Клінічні ознаки еймеріозу перепелів, а саме пригнічення, втрата апетиту, спрага, діарея, реєструються на фоні патоморфологічних змін в тонкій і товстій кишках -лімфоїдно-еозинофільної інфільтрації, катарального запалення слизової оболонки дванадцятипалої кишки; катарально-геморагічного запалення і лімфоїдної інфільтрації слизової оболонки порожньої кишки; еозинофільної інфільтрації, геморагічного запалення слизової оболонки сліпої кишки, скупчення в просвіті останньої геморагічного детриту з спорозоїтами (Gesek, Welenc, Tylicka, Otrocka-Domagała, Paździor, & Rotkiewicz, 2014;Monte, Cavalcante, Oliveira, & Lima, 2015;Yatusevich, Fedotov, Soroka & Orda, 2016).…”
Section: актуальністьunclassified